2022
DOI: 10.2147/jir.s350112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PD-1 Inhibitor Combined with X-Ray Irradiation on the Inflammatory Microenvironment and Lung Tissue Injury in Mice

Abstract: Purpose This study was designed to evaluate the effects of PD-1 inhibitor on lung tissue morphology and the immune system in a mouse model of radiation-induced lung injury (RILI) and to assess interactions between radiation therapy and PD-1 inhibition. Methods Twenty C57BL/6 mice were divided randomly into four groups of five mice each. Mice were treated with an anti-mouse PD-1 monoclonal antibody, whole thorax irradiation, both or neither. Lung tissue morphology and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“… 95 , 96 Recent studies have also revealed that PD-1 is expressed not only on T cells but also on NK cells, B lymphocytes, macrophages and dendritic cells (DCs), 97 , 98 suggesting that PD-1 may play a very effective role in remodeling the tumor immune microenvironment and even systemic antitumor immunity. 46 , 99 102 …”
Section: Ics On T Cellsmentioning
confidence: 99%
“… 95 , 96 Recent studies have also revealed that PD-1 is expressed not only on T cells but also on NK cells, B lymphocytes, macrophages and dendritic cells (DCs), 97 , 98 suggesting that PD-1 may play a very effective role in remodeling the tumor immune microenvironment and even systemic antitumor immunity. 46 , 99 102 …”
Section: Ics On T Cellsmentioning
confidence: 99%
“…In recent years, immune cells and inflammatory cytokines have sparked widespread enthusiasm in the RILI research field [ 30 , 31 ]. IL-2, IL-6 and IL-10 belong to inflammatory cytokines, they can promote inflammatory response through upregulating chemokines, stimulating the secretion of cytokines by various immune cells, inducing acute phase reaction proteins, and coordinating with intracellular signal transduction [ 32 – 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Airway thickness was measured by Vvsub method with ImageJ software ( Mimura et al, 2015 ). Collagen volume fraction was defined as the collagen area/total area of the tissues in the image and analyzed by ImageJ ( Geng et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%